SORPTION OF Au(III) BY Saccharomyces cerevisiae BIOMASS - Amaria Amaria; Suyono Suyono; Eko Sugiharto; Anis N Rohmah (Universitas Gadjah Mada, 2010)
Au(III) sorption by S. cerevisiae biomass extracted from beer waste industry was investigated. Experimentally, the sorption was conducted in batch method. This research involved five steps: 1) identification the functional groups present in the S. cerevisiae biomass by infrared spectroscopic technique, 2) determination of optimum pH, 3) determination of the sorption capacity and energy, 4) determination of the sorption type by conducting desorption of sorbed Au(III) using specific eluents having different desorption capacity such as H2O (van der Waals), KNO3 (ion exchange), HNO3 (hydrogen bond), and tiourea (coordination bond), 5) determination of effective eluents in Au(III) desorption by partial desorption of sorbed Au(III) using thiourea, NaCN and KI. The remaining Au(III) concentrations in filtrate were analyzed using Atomic Absorption Spectrophotometer. The results showed that: 1) Functional groups of S. cerevisiae biomass that involved in the sorption processes were hydroxyl (-OH), carboxylate (-COO-) and amine (-NH2),2) maximum sorption was occurred at pH 4, equal to 98.19% of total sorption, 3) The sorption capacity of biomass was 133.33 mg/g (6.7682E-04 mol/g) and was involved sorption energy 23.03 kJ mol-1, 4) Sorption type was dominated by coordination bond, 5) NaCN was effective eluent to strip Au(III) close to 100%.